Incentivo do cuidado e amamentação com puérperas de Lagarto-SE - Santana, Isabel Cristina da Silva (2019)
INTRODUCTION: For breastfeeding to happen correctly, safely and pleasantly, it is necessary to have a look also towards the mother, regarding self-care: a change in mentality is necessary, in the sense that as important as breastfeeding, taking care of yourself promotes good breastfeeding. The woman-mother needs physical and mental attention, and attention should not be focused only on the child. In this context, the speech therapist comes with his knowledge in acting in the stomatognathic system, collaborating in the work with the mothers in the care of themselves, with actions of attention, comfort and guidance aimed at promoting breastfeeding that strong them and ensure good breastfeeding, with a focused look. To the two protagonists “who breastfeeds and who is breastfed”. GENERAL OBJECTIVE: The present work aims to incentive breastfeeding and analyze the knowledge of postpartum women about self-care, guiding them on the subject. METHODOLOGY: This is a descriptive research. A descriptive analysis of the data was performed in a quantitative and qualitative manner by means of mean, standard deviation, absolute frequency and relative frequency. The data resulting from the questionnaires were analyzed using the Excell program. The research was carried out at Zacarias Júnior Maternity, in the city of Lagarto-SE, through the application of a semi-structured questionnaire in the beds, with the mothers who delivered at the institution, from May to September 2019. The subjects were defined as survey 30 postpartum women, constituting a sample of thirty questionnaires. RESULTS AND DISCUSSION: Thirty postpartum women, participated in the study, 10 with their first child and 20 mothers with two or more children. The reports of the collaborators presented determinants that demonstrated the receipt of guidelines on breastfeeding practice, however, as a negative point found the lack of knowledge about the importance of self-care in this process. A percentage of 33,33% showed the lack of guidance on how to take care of themselves. CONCLUSION: Although most of the mothers are in adulthood and have a history of previous pregnancies, it was noted that a minority is aware of the importance of self-care. In this context, it is noted the importance of the speech therapist in strengthening health education policies aimed at the promotion of breastfeeding and care.